Clinically significant interstitial lung disease in limited scleroderma: histopathology, clinical features, and survival - Fischer, Aryeh; Swigris, Jeffrey J; Groshong, Steve D; Cool, Carlyne D; Sahin, Hakan; Lynch, David A; Curran-Everett, Douglas; Gillis, JoAnn Z; Meehan, Richard T; Brown, Kevin K (Chest, 2008)
To evaluate the pathologic patterns, clinical features, and survival among subjects with scleroderma (ie, systemic sclerosis [SSc]) and clinically significant interstitial lung disease (ILD) evaluated at an ILD center. Retrospective cohort study of all SSc patients who had been referred for further evaluation of ILD and had undergone surgical lung biopsy. Clinical data were abstracted by review of the medical record, and lung biopsy specimens were reviewed and classified according to current pathologic criteria. All patients presented with significant respiratory symptoms. Twenty-two of 27 subjects had surgical lung biopsy-proven ILD, and 5 subjects had miscellaneous non-ILD patterns. Of those subjects with ILD, 64% (14 of 22 subjects) had a nonspecific interstitial pneumonia (NSIP) pathologic pattern (fibrotic NSIP, 13 subjects; cellular NSIP, 1 subject), and 36% (8 of 22 subjects) had the usual interstitial pneumonia (UIP) pattern. Subjects with NSIP were younger (median age, 42 vs 58 years, respectively; p = 0.003), but no differences were noted in pulmonary physiology (FVC: NSIP group, 52% predicted; UIP group, 65% predicted; p = 0.22; diffusing capacity of the lung for carbon monoxide: NSIP group, 40% predicted; UIP group, 42% predicted; p = 1.0). All patients had limited skin involvement. The Scl-70 antibody was absent among those assessed (NSIP group, 0 of 10 subjects; UIP group, 0 of 7 subjects). All patients were treated with cytotoxic therapy. The median survival time for those with NSIP was 15.3 years (5,596 days) compared with 3 years (1,084 days) for those with UIP (p = 0.07 [log-rank test]). In SSc patients with limited cutaneous disease and clinically significant ILD, fibrotic NSIP and UIP are the predominant pathologic patterns. Those with the UIP pattern of disease had a trend toward shorter survival time.